The preferences of breast cancer patients regarding a digital social care platform - Sima Rafiei; Peigham Heidarpoor; Saber Souri; Zahra Nejatifar; Mohammad Amerzadeh (BMC Women's Health)
Abstract Background Breast cancer is a multifaceted condition affecting women globally, with patients often facing emotional, psychological, and social challenges. This study explored breast cancer patients’ preferences for features of a digital social care platform. Methods A cross-sectional study using Conjoint Analysis (CA), grounded in economic utility theory, was conducted. A Discrete Choice Experiment (DCE) questionnaire was administered to 158 breast cancer patients at a university hospital in Iran between November 2023 and January 2024. Data were analysed using ordered logistic regression in Stata 13. Results All platform attributes significantly influenced preferences (P ≤ 0.05). Emotional support had the highest impact (β = 1.132), followed by informational (β = 0.973) and esteem support (β = 0.864). Instructional videos increased the likelihood of choosing a digital platform 2.45 times compared to text-based messages (P < 0.001). Personalized online support was 1.42 times more preferred than generic supportive messages (P < 0.001). Mindfulness affirmations were 1.14 times more preferred than inspirational messages (P < 0.001). Conclusion Digital tools that prioritize emotional, informational, and esteem support—especially through personalized online support and instructional videos can improve patient engagement and acceptability. These findings support the patient-centred design of digital social care platforms to enhance quality of life for breast cancer patients.